Preventing internalizing problems in 6-8 year old children: A universal school-based program - Pophillat, E.; Rooney, Rosanna; Nesa, M.; Davis, Melissa; Baughman, N.; Hassan, S.; Kane, Robert (Frontiers Research Foundation, 2016)
The Aussie Optimism Program: Feelings and Friends (AOP-FF) is a 10 week, universal mental health promotion program based on social/emotional and cognitive and behavioral strategies. The aim of the current study was to evaluate the efficacy of a universal Cognitive Behavioral Therapy based program in preventing and reducing internalizing problems in 6-8 year olds (Years 1-3 in Australia). Year 1-3 students from a low SES primary school (N = 206) were randomly assigned in classes to either an intervention or a control group and assessed at baseline and post-test. Results showed a significant (p = 0.009) and small to moderate (partial eta-squared = 0.034) pre-post decrease in parent-reported anxiety symptoms for the intervention group, in conjunction with a non-significant (p = 0.708) and negligible (partial eta-squared = 0.001) pre-post increase for the control group. A larger randomized controlled trial assessing longer term effects is needed. In addition the program needs to be simplified for year 1-2 students with a separate more developmentally appropriate program for year 3 students.